2012
DOI: 10.1088/1748-0221/7/06/p06001
|View full text |Cite
|
Sign up to set email alerts
|

Expected radiation damage of reverse-type APDs for the Astro-H mission

Abstract: Scheduled for launch in 2014, Astro-H is the sixth Japanese X-ray astronomy satellite mission. More than 60 silicon avalanche photodiodes (Si-APDs; hereafter APDs) will be used to read out BGO scintillators, which are implemented to generate a veto signal to reduce background contamination for the hard X-ray imager (HXI) and a soft gamma-ray detector (SGD). To date, however, APDs have rarely been used in space experiments. Moreover, strict environmental tests are necessary to guarantee APD performance for miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…[52][53][54][55] The BGO crystal is dense (7.1 g∕cm 3 ), has a high stopping power (i.e., short radiation length of 1.1 cm), high optical transparency, and ability to form a large crystal although its light output is lower than NaI or CsI.…”
Section: Bgo Active Shield and Support Structurementioning
confidence: 99%
“…[52][53][54][55] The BGO crystal is dense (7.1 g∕cm 3 ), has a high stopping power (i.e., short radiation length of 1.1 cm), high optical transparency, and ability to form a large crystal although its light output is lower than NaI or CsI.…”
Section: Bgo Active Shield and Support Structurementioning
confidence: 99%
“…Strictly speaking, however, this is too optimistic because the APD suffers bulk damage mainly caused by high energy protons as well as surface damage demonstrated by 60 Co irradiation. In fact, Kataoka et al [16] reported that significant increase in bulk current, which is the multiplied component of the APD dark current. Assuming that about 5 percent of the total dose will be attribute to high energy protons, they concluded that the energy threshold of the BGO readout for Astro-H may increase by a factor of 1.3-1.6 after the expected five-year life of the Astro-H mission, whereby its impact on background rejection power must be carefully considered before the launch.…”
Section: Radiation Tolerance Testmentioning
confidence: 99%
“…The dark current is composed of surface current and bulk current (with only the latter being multiplied in proportion to the avalanche gain) [16]. At the in-orbit temperature the bulk current should be dominant, while at room temperature it is not clear which component is responsible for the net dark current.…”
Section: Pre-flight Model Apd Acceptance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (left). We employ existing technologies developed for ASTRO-H [5] and micro-satellite TSUBAME [6] to quickly realize the WF-MAXI mission.…”
Section: Introductionmentioning
confidence: 99%